2019
DOI: 10.7150/jca.34806
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxymethylcytosine and ten-eleven translocation dioxygenases in head and neck carcinoma

Abstract: Ten-eleven translocation (TET) enzymes are implicated in DNA demethylation through dioxygenase activity, which converts 5-methylcytosine to 5-hydroxymethylcytosine (5-hmC). However, the specific roles of TET enzymes and 5-hmC levels in head and neck squamous cell carcinoma (HNSCC) have not yet been evaluated. In this study, we analyzed 5-hmC levels and TET mRNA expression in a well-characterized dataset of 117 matched pairs of HNSCC tissues and normal tissues. 5-hmC levels and TET mRNA expression were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Although DNA methylation and its mechanism are well studied, DNA hypomethylation and demethylation are poorly understood in HNSCC (8,17). In a previous study, we showed that altered levels of 5-hmC were associated with tumorigenesis, and that lower 5-hmC levels were correlated with reduced survival (16). On the other hand, the current study is the rst to examine LINE-1 hypomethylation levels and 5-hmC levels in HNSCC.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Although DNA methylation and its mechanism are well studied, DNA hypomethylation and demethylation are poorly understood in HNSCC (8,17). In a previous study, we showed that altered levels of 5-hmC were associated with tumorigenesis, and that lower 5-hmC levels were correlated with reduced survival (16). On the other hand, the current study is the rst to examine LINE-1 hypomethylation levels and 5-hmC levels in HNSCC.…”
Section: Discussionmentioning
confidence: 60%
“…Several studies have also shown that 5-hmC is an intermediate of DNA demethylation (25). Immuno-based assays are the most commonly used, including ELISA, and these methods utilize available antibodies speci c to 5-hmC to avoid crossreactivity with 5-mC and unmethylated cytosine (16). Moreover, 5-hmC depletion could signi cantly contribute to genome instability and inaccurate chromosome segregation, perhaps explaining the correlation between low 5-hmC levels and cancer (26).…”
Section: Discussionmentioning
confidence: 99%
“…Although DNA methylation and its mechanism are well studied, DNA hypomethylation and demethylation are poorly understood in HNSCC (8,17). In a previous study, we showed that altered levels of 5-hmC were associated with tumorigenesis, and that lower 5-hmC levels were correlated with reduced survival (16). However, the current study is the rst to examine LINE-1 hypomethylation levels and 5-hmC levels in HNSCC.…”
Section: Discussionmentioning
confidence: 70%
“…Several studies have also shown that 5-hmC is an intermediate of DNA demethylation (25). Immuno-based assays are the most commonly used, including ELISA, and these methods utilize available antibodies speci c to 5-hmC to avoid crossreactivity with 5-mC and unmethylated cytosine (16). Moreover, 5-hmC depletion could signi cantly contribute to genomic instability and inaccurate chromosome segregation, perhaps explaining the correlation between low 5-hmC levels and cancer (26).…”
Section: Discussionmentioning
confidence: 99%
“…In solid tumors, 5hmC is depleted compared to normal tissue [ 20 ] and some studies show that a lower 5hmC level is associated with poorer outcome [ 21 – 23 ]. When 5hmC is depleted, the mark is lost at genic regions, particularly around transcription start sites (TSS) and in gene bodies [ 24 ].…”
Section: Introductionmentioning
confidence: 99%